Optimizing Conditions for The Production Process of Cashew Apple Juice (Anacardium Occidentale L.) From Binh Phuoc (Viet Nam) Using Response Surface Methodology (RSM) - Hanh, Nguyen Thi; Trang, Nguyen Thi; Lap, Tuong Van; Hung, Nguyen Van; Trang, Vu Thu; Long, Nguyen Viet; Thuy, Nguyen Thi (International Journal of Membrane Science and Technology, 2023)
Cashew apple is one of the promising food material sources because this fruit contains high nutrtional values. This study aims for developing cashew apple juice into a new beverage and contributing to increase economic value for the byproduct of cashew industry. In this study, by using Reponse surface methodology (RSM), four different factors (juice concentration, %acid, %aroma, Brix) in mixing cashew apple juice product were examined to determine their optimum value in order to obtain the highest acceptance of the final product. The results of performed experiments showed that the combination of juice concentration 36%, acid 0.32%, aroma 0.017% and 13.7oBx gave the highest acceptance (6.925/9).